Ethical and Religious Analysis on Euthanasia. - Shuriye, Abdi Omar (IIUM Press, 2011)
This paper is an analysis on euthanasia from ethical and religious perspectives. Historically, the classical Greek thinkers including Aristotle had categorically accepted euthanasia with the main reason of minimizing pain. However, as science develops ethical and religious issues related to the subject have increasingly created fervent debates on euthanasia.